2006
DOI: 10.1002/cpp.502
|View full text |Cite
|
Sign up to set email alerts
|

Cautions on the overgeneralized application of the NICE and CREST recommendations for the treatment of PTSD in the UK: a reflection from practice in Belfast, Northern Ireland

Abstract: The task of this paper is to present a message of caution regarding the overgeneralized reliance on the NICE (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…They found that 12% of their community sample met the criteria for post traumatic stress disorder (PTSD) and that this was also related to socio-economic status. Dorahy (2006) has made the important point that conventional treatment for PTSD may not be sufficient in Northern Ireland as the nature of Troubles-related trauma and the sociopolitical, ethno-cultural context may require a range of different responses. Tomlinson (2007) in his report, The Trouble with Suicide concluded that:…”
Section: The Impact Of 'The Troubles' On Mental Health In Northern Irelandmentioning
confidence: 99%
“…They found that 12% of their community sample met the criteria for post traumatic stress disorder (PTSD) and that this was also related to socio-economic status. Dorahy (2006) has made the important point that conventional treatment for PTSD may not be sufficient in Northern Ireland as the nature of Troubles-related trauma and the sociopolitical, ethno-cultural context may require a range of different responses. Tomlinson (2007) in his report, The Trouble with Suicide concluded that:…”
Section: The Impact Of 'The Troubles' On Mental Health In Northern Irelandmentioning
confidence: 99%
“…In the light of their investigations regarding the concept of "complex PTSD", Dorahy (2006) and Harrison and McGoran (2008) argue that the treatments recommended by NICE and the Clinical Resource Efficiency and Support Team (CREST), namely Trauma Focused Cognitive Behavioural Therapy (TF-CBT) and Eye Movement Desensitisation and Reprocessing (EMDR) may not be appropriate for the treatment of more complex presentations of PTSD from individuals who have experienced chronic and incessant violence or multiple traumatic events. Harrison and McGoran (2008), following results from an audit of cases in the Family Trauma Centre, suggest a phased approach to treatment of such cases which modifies the current NICE guidelines and addresses the "complex socio-political aspect".…”
Section: Discussionmentioning
confidence: 98%
“…It has also been noted, however, that the Northern The experience and psychological impact of 'Troubles' related trauma in Northern Ireland 101 Ireland "Troubles" present a complex array of incidents which in turn are set in a variety of social contexts. In recent years, a number of authors have questioned the homogeneity of PTSD presentations associated with the "Troubles" given these discrepancies (Dorahy, 2006;Harrison & McGoran, 2008;Dorahy et al, 2009). These authors have explored the concept of "complex PTSD" and whether this construct better characterises presentations of symptoms from individuals exposed to intense and sustained violence or multiple traumatic events.…”
Section: Please Scroll Down For Articlementioning
confidence: 96%
See 2 more Smart Citations